2021
DOI: 10.1002/hed.26656
|View full text |Cite
|
Sign up to set email alerts
|

Association between sex and survival in patients with head and neck spindle cell carcinoma

Abstract: Background Head and neck spindle cell carcinoma (HNSpCC) is a rare histological variant associated with worse outcomes. Our objective was to identify clinicopathological factors associated with survival in patients with HNSpCC compared to patients with conventional head and neck squamous cell carcinoma (HNSCC). Methods Using clinical data from the Surveillance, Epidemiology, and End Results database, we performed a survival analysis in patients with HNSpCC or HNSCC between 2004 and 2016. Results A total of 458… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…One study of HNSpCC using the SEER registry identified an association between female sex and poorer DSS. 27 This finding was explained by the estradiol-induced overexpression of epithelial-mesenchymal transition (EMT) transcription factors and the deregulation of EMT-related microRNA, both of which contribute to HNSpCC carcinogenesis. 73,74 Interestingly, our study failed to detect significance between female sex and OS in multivariate analysis that included all HNSpCC cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One study of HNSpCC using the SEER registry identified an association between female sex and poorer DSS. 27 This finding was explained by the estradiol-induced overexpression of epithelial-mesenchymal transition (EMT) transcription factors and the deregulation of EMT-related microRNA, both of which contribute to HNSpCC carcinogenesis. 73,74 Interestingly, our study failed to detect significance between female sex and OS in multivariate analysis that included all HNSpCC cases.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6,20,35,36 Across all head and neck primary sites, patients with HNSpCC had higher-grade tumors, aligning well with existing literature. 6,27,30,37,38 The HR for death significantly varied by histology in multivariate analysis that included all HNSpCC and HNSCC cases. Multivariate analyses repeated within each primary site cohort, however, suggest that SpCC histology is not an independent prognostic factor when compared with conventional SCC for every head and neck primary site, supporting previous conclusions that SpCC and SCC may behave similarly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations